Nursery grounds of jatka (juvenile hilsa, Tenualosa ilisha) in the major rivers of Bangladesh - Rashid, Md. Harunor; Sarker, S. M. Nurul Amin Harmuj Ali; Arshad, Aziz; Md. Yusoff, Fatimah (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
The study evaluate the abundance and distribution of juvenile hilsa, Tenualosa ilisha in four major rivers (Padma, Meghna, Jamuna, Brahmaputra Surma and Andermanik) of Bangladesh to from February to April 2017. Fish samples were collected using monofilament gill net. The total length and depth of the gill net was 100 meter and 4.5 meter, respectively. The mesh size of the nets used were 2.5, 3.5, 4.5 and 5.5 cm. Daytime sampling was carried out at all the sites on monthly basis and the Catch per Unit Effort (CPUE), total length (cm) and weight (gm) were recorded and analysed. The result showed that the highest CPUE of juvenile hilsa was observed at Ramgati station with catch of 72 individual/100m gill net/30 minutes. The second and third highest CPUE was in Nalchira, 58 individual/100m net/ 30 min, and Charking, 46 individual/100m net/ 30 min, located in the lower Meghna region. There was a significance variation (P < 0.05) of CPUE among the 18 stations. Juvenile hilsa was found to be highly abundance in the lower Meghna River as compared to the upper part of the rivers. The abundance of juvenile hilsa was the highest in March, 19 individual/100m net/30min, and the lowest in April, 14 individual/100m net/30 min. There was no significant difference observed among the months. The study indicated that hilsa juvenile were distributed all over the months from lower to upper part of the rivers. The average length of juvenile in February, March and April were 9.18±0.10cm, 15.94±0.17cm and 22.11±0.18cm, respectively. It was also observed that the average weight of juvenile in February was 9.88± 0.25gm, 41.16± 1.48gm in March and 100.94± 1.29gm in April, respectively. During the study period jatka was absent in the upper areas of Padma, Jamuna and Surma rivers. It may be concluded that the major nursery grounds is located between Chandpur and Hatya of Meghna River.